Effect of the addition of rabbit meat on the technological and sensory properties ofermented sausage - Ignacio, Eduardo Oliveira; Santos, João Marcos Dos; Santos, Sylvio Eduardo Di Jacintho; Souza, Camila Vespúcio Bis [UNESP]; Barretto, Andrea Carla da Silva [UNESP] (FapUNIFESP (SciELO), 2020)
Rabbit meat has a low-fat content when compared to other meat traditionally used as raw material in the processing of fermented sausages. In addition, it has high levels of essential amino acids in its composition. Thus, the objective of this study was to evaluate the technological properties and sensorial acceptance of a fermented sausage produced with pork and rabbit meat. Three formulations were made: C1 (80% fresh lean pork + 20% pork back fat), T1 (40% fresh lean pork + 40% rabbit meat + 20% pork back fat) and T2 (80% rabbit meat + 20% pork back fat). Samples were evaluated for composition, texture profile, instrumental color, pH, weight loss, lipid oxidation and sensorial acceptance. The samples did not present significant differences between them for moisture, fat and protein contents. Regarding the aroma, flavor, hardness and overall acceptance, all samples presented similar mean values (P>0.05). The study showed that up to 40% of rabbit meat could be substituted in a fermented pork sausage without altering any of the sensorial attributes evaluated and with minimal effect on the technological parameters.
Keywords: Fermented products; Rabbit sausage; Sensory acceptabilit; Texture profile analysis